Penampilan Genotipe Varietas Jagung lntroduksi di Lahan Lebak Dangkal Kalimantan Selatan - , Nurtirtayani; H. Suaidi Raihan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The problems of monotoon swamps are acid soil and macro nutrient deficient, especially P and K. To solve the problems, it can be used the tolerant and adapted varieties at monotoon swamp. Fourteen genotypes from CIMMYT (Mexico), two national varieties and two local varieties as check varieties were tested in randomized block design with three replication in dry season of 2000 at Sungai Kupang village, Hu/u Sungai Selatan district. The result of experiment indicated that two genotypes have highest yield; i.e. Cotaxtla S 9649 and Synthetic NVE - SR (TIWD). And then. there were four genotypes have lower yield than Cotaxtla S 9649 and Synthetic NVE - SR (TIWD). Yield of the other genotypes were not significantly different with local variety. The day to mature of the whole genotypes were 90 days.   Key words: Performance, Genotypes/varieties, Corn. Monotoons swamp.